Excavating the Relation Between Non-Being and Permanence in the Vedas, Upanishads, Bergson, Deleuze and Vaddera Chandidas. Issue 1 (February 2018) - Raghuramaraju, A.
Abstract : In the context of discussing Deleuze's account of Bergson's idea of non-being, this paper brings into discussion different versions of non-being as available in Indian philosophy. These versions are drawn both from classical Indian philosophy including Vedas and Upanishads and modern Indian philosophy such as Vaddera Chandidas. The paper discusses Deleuze's analysis of Bergson on the relation between non-being and negation. While Bergson rightly traces the roots of non-being to negation, he, however, rendered it to intuition. Extending Bergson's diagnosis of negation as the basis of non-being, the paper goes on to show, using Chandidas's work Desire and Liberation: The Fundamentals of Cosmicontology, how negation in the form of pre-existence and post-existence that negate existence is made possible by permanence. Pre- and post-existence are permanent; in contrast, existence is rendered impermanent and changing. The paper concludes, using the insights from Chandidas, by exposing this conspiracy of metaphysics that renders the real existence as fleeing and impermanent in contrast to the non-being that is projected by the intellect as real.